Racing beyond race: Western press reportage of 2008 American presidential campaign (2014)
The 2008 American presidential campaign was a critical moment for determining the stance of Western Press in the coverage of a race-related political contest. The study content analysed The Economist. Time and Newsweek magazines to identify the genre, slant, source of news reports and prominence given to Barack Obama Campaign Issues relative to those of his opponents. John McCain and Hilary Clinton. Although there were a few elements of racial constructs. reportage was found to be fair focusing more on Obama campaign issues (64.8 percent) than McCain (33.4 percent) and Clinton (1.8 percent)campaign issues. Reported mostly as Features, stories provided in-depth and holistic examination of Obama, guiding voter decision making. News coverage transcended racial sentiments and addressed socioeconomic and political matters that appealed to the American people. The paper points to the gatekeeping and agenda setting roles of Western Press and their implication for electioneering processes and outcomes.